Social exchange and communication networks among Malaysian academic scientific community - Abu Hassan Othman (Universiti Kebangsaan Malaysia, 1980)
This paper reports on the participation of academic-based Scientists in Malaysia in social exchange and communication networks with their "significant colleagues" both within and without their institutions, with Malaysian and as well as with their foreign counterparts who are based in their institutions. The focus of analysis will be on (a) Scientists'' (b) Interpersonal ties, with foreign scholars in scientists' own institutions, and (c) Scientists' participation in the local Malaysian scientific gatherings.